2019
DOI: 10.1002/jor.24498
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ibuprofen on Bone Healing After Colles' Fracture: A Randomized Controlled Clinical Trial

Abstract: Non‐steroidal anti‐inflammatory drugs (NSAIDs) may delay bone healing. [Therefore, it is important to establish whether NSAID preparations delay bone healing and what correlations, if any, exist between different bone studies—DEXA—scanning, bone markers, roentgenology controls, and histological examination of newly formed bone]. The purpose of this prospective controlled study was to investigate whether ibuprofen affects bone mineral density, turnover biomarkers, and histomorphometric characteristics of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…In a recent small RCT ( n = 128) of open reduction and internal fixation of ankle fractures, ketorolac vs. no ketorolac had no effect on clinical or radiographic healing assessed by blinded observers at 12 weeks postoperatively [ 20 ]. A randomized controlled trial (RCT) in patients with Colles’ fracture ( n = 95) showed no difference in outcome between the groups receiving ibuprofen and placebo [ 21 ]. In another more recent multicenter observational study, NSAID use versus opioid use after intermedullary nailing of diaphyseal tibia fractures ( n = 372) had no effect on healing time [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent small RCT ( n = 128) of open reduction and internal fixation of ankle fractures, ketorolac vs. no ketorolac had no effect on clinical or radiographic healing assessed by blinded observers at 12 weeks postoperatively [ 20 ]. A randomized controlled trial (RCT) in patients with Colles’ fracture ( n = 95) showed no difference in outcome between the groups receiving ibuprofen and placebo [ 21 ]. In another more recent multicenter observational study, NSAID use versus opioid use after intermedullary nailing of diaphyseal tibia fractures ( n = 372) had no effect on healing time [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…С другой стороны, серия наблюдательных исследований, проведенных в последнее время, показала отсутствие негативного влияния НПВП на консолидацию переломов ЛК и костей голени [22][23][24][25]. По результатам метаанализа 13 исследований (3 клинических и 10 экспериментальных), проведенного К. Duchman и соавт.…”
Section: факторunclassified
“…Furthermore, various reports have suggested that NSAIDs interfere with bone healing, though others have contradicted these findings [7]. Celecoxib [8,9] and aspirin [10] inhibit bone healing [11,12], while ibuprofen [13] and parecoxib [14] do not affect bone healing.…”
Section: Introductionmentioning
confidence: 99%